(untitled) (Medical Forum Monthly, 2023)
Objective: This paper presents postmortem and histological data in order to clarify the inner progression of methanol intoxication. The research will also examine the histological, biochemical, and clinical changes brought on by methanol poisoning. Study Design: Descriptive cross-sectional investigation. Place and Duration of Study: This study was conducted at the Department of Forensic Medicine and Toxicology, DHQ, Rawalpindi, Rawalpindi Medical University, Rawalpindi from January 2022 to October 2022. Materials and Methods: Four persons were brought in dead; four of them passed away shortly after being admitted (early deaths), five of them passed away between 10 and 45 days after being admitted to the hospital (late deceases). Each of the 13 victims had a medico-legal autopsy. Gross exterior and internal results were recorded, and routine blood and viscera conservation & transfer to the lab for methyl alcohol analysis were also carried out. From the optic chiasma, a section of the nerve that supplies vision was removed for histological analysis. Information was gathered using old records. Results: Their age ranged from 20 to 60 years old, and 70% (n = 10) of all fatalities were between 25 and 55 years old. The average methyl alcohol concentration was 107.12 mg/dl and 236.8 mg/dl, respectively, among hospital fatalities and brought deceased. Vomiting and stomach discomfort were the most frequently reported symptoms (n = 8), followed by poor eyesight (77%), and indicators of respiratory insufficiency (52%). Hospitalization deaths had average bicarbonate & pH values of 7.29 and 7.72mmol/l, correspondingly. An autopsy revealed that each person had hypoxia. The obstruction affected internal organs. In the early instances, serious acidosis of the metabolism that led to respiratory failure was the cause of death. As a consequence of septicemic shock, brain and pulmonary edoema led to late deaths. Cerebral edoema and intracerebral haemorrhage were seen in the patient with the longest survival duration. Another internal finding in late deaths was the presence of cirrhotic liver together with symptoms of renal failure. The optic nerve's histopathology showed modest edematous changes rather than demyelination or axonal necrosis. Conclusion: Poisoning by methanol. The many organs and organ systems of the body have a number of detrimental effects. Many lives may be saved with an early diagnosis and treatment. Organ-directed, accurate autopsies may help autopsy surgeons make diagnoses and, as a result, can help the legal system bring perpetrators to justice.